CÁC HỢP CHẤT MEGASTIGMAN VÀ PHENYLPROPANOID PHÂN LẬP TỪ CÂY GỪA (FICUS MICROCARPA) - Cường, Nguyễn Xuân; Kiệm, Phan Văn; Minh, Châu Văn; Hải, Trương Nam; Nhiệm, Nguyễn Xuân; Thư, Vũ Kim; Tuấn Anh, Hoàng Lê; Yến, Phạm Hải; Thảo, Nguyễn Phương; Nam, Nguyễn Hoài; et al. (Vietnam Journal of Chemistry, 2012)
Three megastigmanes, bridelionoside B (1), (3S,5R,6R,7E,9S)-megastigmane-7-ene-3,5,6,9-tetrol (2), and dihydroalangionoside A (3), and one phenylpropane glucoside, syringin (4) were isolated from the methanol extract of Ficus microcarpa leaves. Their structures were elucidated by spectroscopic methods including ESI-MS, 1D- and 2D-NMR in comparison with the literature values. Keywords: Ficus microcarpa, Moraceae, megastigmane.